1982
DOI: 10.2136/sssaj1982.03615995004600050019x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Availability under Trickle Irrigation: I. Distribution of Water and Bray no. 1 Phosphate

Abstract: The distribution of water and Bray no. 1 phosphate was measured in the surface soil of a Chromic Luvisol that had been under trickle irrigation for 5 years. The region of the soil reaching field capacity after 8 to 12 h of irrigation extended horizontally to at least 65 and up to 90 cm from the outlet and was no deeper than 12 cm from the surface. After irrigation had ceased soil water decreased with time but usually did not become significantly different from field capacity until after about 24 h.Where the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Conversely, several studies have observed P leaching, to varying degrees, from sand‐based systems (Bacon and Davey, 1982; Kargbo et al, 1991; Shuman et al, 2000; Shuman, 2002). However, researchers in their respective studies primarily attributed P leaching to the inadequate turfgrass root system development during the EST year which reduced P uptake (Shuman et al, 2000), excessive rates of P fertilization (Shuman, 2002), or leaching during increased irrigation, high rainfall events, or both (Bacon and Davey, 1982; Kargbo et al, 1991; Shuman, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, several studies have observed P leaching, to varying degrees, from sand‐based systems (Bacon and Davey, 1982; Kargbo et al, 1991; Shuman et al, 2000; Shuman, 2002). However, researchers in their respective studies primarily attributed P leaching to the inadequate turfgrass root system development during the EST year which reduced P uptake (Shuman et al, 2000), excessive rates of P fertilization (Shuman, 2002), or leaching during increased irrigation, high rainfall events, or both (Bacon and Davey, 1982; Kargbo et al, 1991; Shuman, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Values were similar for both irrigation methods at Quincy. Bacon and Davey (1982) suggested that the higher soil moisture associated with drip irrigation resulted in cyclic release of native and applied phosphates by reduction of amorphous iron phosphates during the anaerobic phase of the irrigation cycle, thus increas- Table 3. Phosphorus concentration of squash as affected by location, irrigation method, N-K rate, and N-K application time.…”
Section: Resultsmentioning
confidence: 99%
“…Movement of phosphorus in soils is very limited. However, drip irrigation improves notoriously the mobility of phosphorus (P) in soil, relative to conventional irrigation, when it is applied at low rates (Bacon et al, 1982-a) [2] . Potassium (K) moves to a limited extent in the soils but drip irrigation improves its mobility (Kafdafi et al, 1980) [13] .…”
Section: Fertilizer Use Efficiencymentioning
confidence: 99%